Investigating Cadets’ Experiences Learning English at a Banyuwangi Marine Academy in the Global Maritime Era - Khoiruman, Muhamad Alfi; Irawan, Doni Hadi; Rohmah , St. Shabibatul (LinguaEducare: Journal of English and Linguistic Studies, 2026)
In the era of global maritime communication, English plays a vital role as a working language for safety, coordination, and professional interaction within the international maritime industry. This study explores marine cadets’ experiences in learning English as a General Course at a Banyuwangi Marine Academy, with particular attention to how the course supports their communicative needs in maritime contexts. Employing a qualitative research design, data were collected through semi-structured interviews and classroom observations involving selected cadets enrolled in the English General Course. The data were analyzed thematically to identify recurring patterns related to perceptions, learning challenges, and instructional practices. The findings reveal that although cadets perceive English as highly important for their future maritime careers, they consider the course insufficiently contextualized to real maritime communication demands. Key challenges include limited speaking confidence, inadequate mastery of maritime-specific terminology, and anxiety in oral communication activities. Observational data further indicate that instructional practices are predominantly teacher-centered and emphasize grammatical knowledge over communicative and experiential learning. As a result, opportunities for meaningful interaction and practical language use remain limited. This study highlights a mismatch between curriculum design and cadets’ professional expectations in the context of global maritime operations. The findings suggest the need to reconceptualize English as a General Course by integrating maritime-oriented content, learner-centered pedagogy, and communicative activities that reflect authentic maritime scenarios. Such improvements are essential to enhance cadets’ communicative competence and readiness for participation in the global maritime workforce.